Mitigating of Paracetamol-induced Hepatotoxicity in Albino Mice Using Boerhaavia diffusa Extracts - Goswami, Praveen; Damor, Shilpi; Kaushik, Utkarsh (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
Boerhaavia diffusa, renowned for its therapeutic efficacy in chronic liver diseases, operates through multifaceted mechanisms to uphold internal homeostasis. Its pivotal roles encompass modulation of intermediary metabolism of macromolecules, synthesis of crucial plasma proteins, enzymatic activities, and bile excretion.In this investigation, we aimed to evaluate the hepatoprotective potential of Boerhaavia diffusa against paracetamol-induced hepatotoxicity in rats. Our study revealed promising outcomes as the extracts obtained from Boerhaavia diffusa demonstrated a significant hepatoprotective role in albino rats subjected to hepatotoxicity induced by paracetamol administration. During the study, the animals were administered doses of 1g/kg b.wt and 2 g/kg b.wt of the plant extracts. Following paracetamol administration, conspicuous changes were observed in hepatocyte biochemical markers, indicative of hepatotoxicity. However, treatment with Boerhaavia diffusa extracts ameliorated these alterations, underscoring their potential to mitigate paracetamol-induced liver injury. These findings underscore the significant hepatoprotective properties inherent in the plant extracts derived from Boerhaavia diffusa. which can be utilized as a potential therapeutic avenue for the management of paracetamol-induced liver damage. These findings hold promise for the development of novel therapeutic interventions aimed at safeguarding liver health and mitigating the adverse effects of hepatotoxic insults.